(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
Education begins not only in schools but also with the parents, who are the first teachers of the children. A child’s development, character, and personality are shaped directly by the attitudes and values within the family environment. In this blog post, we will closely examine the role of families in children’s education and their impact on development. Let’s explore how good education provided by families reflects in children’s lives.